Optical Resolution of the Water-Soluble Ti4(embonate)6 Cages for Enantioselective Recognition of Chiral Drugs - He, Yan-Ping; Yuan, Lv-Bing; Song, Jin-Shuai; Chen, Guang-Hui; Lin, Qipu; Li, Chunsen; Zhang, Lei; Zhang, Jian (Chemistry of materials, 2018)
Synergetic optical resolution and chiral amplification of tetrahedral Ti4L6 cages by enantiopure coordination cations have been realized in this work. Anionic ΔΔΔΔ-[Ti4L6] and ΛΛΛΛ-[Ti4L6] cages (L = embonate) have been completely resolved by enantiopure Λ-[Mn(1R,2R-DCH)3] and Δ-[Mn(1S,2S-DCH)3] cations, respectively. Accordingly, two homochiral compounds (PTC-108(Δ) and PTC-108(Λ)) with three-dimensional supramolecular architectures were formed, containing larger diamondoid cages. Such an unusual resolution process clearly shows the stepwise transfer of homochirality from an enantiopure molecule to a resolved hydrogen-bonding aggregation and a final homochiral framework. Moreover, the separated homochiral Ti4L6 cage presents enantioselective recognition toward chiral organic and pharmaceutical molecules. This work opens a novel resolution-dependent homochiral framework construction approach, and it also takes the homochiral tetrahedral Ti4L6 cages with high solubility and stability into promising enantioselective application.